Early intervention for behaviour problems in young children with developmental disabilities - Roberts, Clare; Mazzucchelli, T.; Taylor, Kelly; Reid, Roisin (Routledge, 2003)
This article reviews research on intervention for young children with dual developmental and behavioural problems. It makes a case for intervention to include family variables and to occur in the preschool years. Behaviour problems are common in young children with developmental disabilities. If untreated these problems are likely to persist and become more challenging and severe in adulthood. Behaviour problems interfere with cognitive, social and emotional development, create additional family stress, often lead to exclusion from community services, and result in additional financial costs to the community. Intervention research provides some support for the effectiveness of parent management training and interventions based upon applied behaviour analysis. However, randomised controlled trials with adequate follow-up periods are required, along with the measurement of outcomes for the family as a whole.